The new Hamas document: An analytical reading of its development and application - Ahmed ALMadani (Faculty of Social and Political Science, Universitas Airlangga, 2017)
The Palestine Liberation Organization (PLO) has been the sole legitimate representative of the Palestinian people since the creation of the Palestinian. The PLO adopted the option of armed struggle against the Israeli occupation, but ended with the signing of the Oslo accords between the Palestine Liberation Organization and Israel in the 1990s. The Islamic Resistance Movement in Palestine (Hamas) was established in the 1980s. Hamas developed its political ideas through a new political document resulted in a new vision to resolve the Palestinian-Israeli conflict by transforming the conflict from religious conflict to political conflict and accepting the establishment of a Palestinian state on the 1967 borders as a common ground between the Palestinian movements and parties, while the armed struggle remains a path of resistance. The purpose of this article is to truly understand this development and the possibility of its application on the ground or not, by clarifying the differences between the ideas of the former and the new Hamas, The researcher relied on a number of academic articles and political research in addition to the political TV shows that talked about the new document, the Arab and international positions of this document, The result of this article is that the Palestinian Hamas movement as a Palestinian resistance movement is capable of political development and finding the alternatives available to solve the Palestinian file while preserving the Palestinian national constants. The Conclusion is the Palestinian Hamas movement is developing with the developments of regional and international events and political development has been partially accepted internationally, Hamas have to work more in the political field to balance between political development and the Palestinian constants.